2018
DOI: 10.1007/s00401-018-1806-2
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes facilitate brain metastasis of breast cancer by inducing Guanylate-Binding Protein 1 expression

Abstract: The discovery of genes and molecular pathways involved in the formation of brain metastasis would direct the development of therapeutic strategies to prevent this deadly complication of cancer. By comparing gene expression profiles of Estrogen Receptor negative (ER-) primary breast tumors between patients who developed metastasis to brain and to organs other than brain, we found that T lymphocytes promote the formation of brain metastases. To functionally test the ability of T cells to promote brain metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 58 publications
4
75
0
Order By: Relevance
“…A recent study showed that GBP1 may promote lung adenocarcinoma invasiveness by stimulate cell motility and via manage of GBP1 expression may development of new therapeutic ways for tumor 30 . GBP1 also found as a fetal T lymphocyte-induced protein that cause breast cancer cells to cross the blood-brain barrier 31 . Our results showed that higher mRNA expressions of GBP1 were found in HNSCC tissues, and that mRNA expression of GBP1 was significantly related with patients' cancer stages and abundance of immune infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that GBP1 may promote lung adenocarcinoma invasiveness by stimulate cell motility and via manage of GBP1 expression may development of new therapeutic ways for tumor 30 . GBP1 also found as a fetal T lymphocyte-induced protein that cause breast cancer cells to cross the blood-brain barrier 31 . Our results showed that higher mRNA expressions of GBP1 were found in HNSCC tissues, and that mRNA expression of GBP1 was significantly related with patients' cancer stages and abundance of immune infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been found in squamous head-and-neck cancers, where GBP1 expression correlates with disease stage and lymph node metastasis in patient samples (63,64). GBP1 expression has also been correlated with metastasis in both lung and breast cancers as well, where study of human lung cancer explants and brainmetastasizing breast cancer cells showed decreased migration in vitro upon GBP1 blockade and GBP1 expression correlated with disease progression in patients (54,65). Intriguingly, in breast cancer metastasis, it was found that GBP1 expression was induced in breast cancer cells by T-lymphocyte activity, showing that cancer-extrinsic processes may influence GBP1's context and function (54).…”
Section: Gbp1 In Cancermentioning
confidence: 99%
“…Cancer emerges from a complex interplay of mutational events and cell state transitions that are accompanied by interferonmediated inflammation and cytoskeletal reorganization which may involve GBP1 in the oncogenic process. The effects of GBP1 in cancer appear to be highly context-dependent, however, as its upregulation is associated with decreased progression in some cancer types, such as breast and colorectal cancer (51-53), but is linked with increased progression, metastasis, and treatment resistance in other cancer types, such as ovarian cancer and glioblastoma (17,54). Although GBP1 may exert these effects in a cancer-intrinsic manner by acting within cancer cells or via a cancer-extrinsic mechanism through microenvironment and immune activity, current literature does not yet distinguish clearly between these contributions and additional investigation is urgently needed.…”
Section: Gbp1 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…While the biologic basis of the relationship between posttreatment NLR and success of treatment is quite complex. It is true that lymphopenia is correlated with a poor prognosis, while a preclinical study found that activated T cells could facilitate BM through inducing an elevated expression of Guanylate-Binding Protein 1 (GBP1) by the cancer cells (26). Moreover, neutropenia increase the risk of infections.…”
Section: Discussionmentioning
confidence: 99%